2013
DOI: 10.1016/j.maturitas.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The DietCompLyf study: A prospective cohort study of breast cancer survival and phytoestrogen consumption

Abstract: DietCompLyf is a multi-centre prospective study designed to investigate associations between phytoestrogensnaturally occurring plant compounds with oestrogenic properties -and other diet and lifestyle factors with breast cancer recurrence and survival. 3159 women with grade I-III breast cancer were recruited 9-15 months postdiagnosis from 56 UK hospitals. Detailed information on clinico-pathological, diet, lifestyle and quality of life is collected annually up to 5 years. Biological samples have also been coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Fink and colleagues (32) reported a decreased allcause mortality in patients with pre-and postmenopausal breast cancer who had a high intake of isoflavones, whereas a reduced breast cancer-related mortality was observed in postmenopausal women. However, the DietCompLyf study (33), which investigated associations between phytoestrogens and breast cancer recurrence and survival, found no significant associations between prediagnosis phytoestrogen intake and reduced breast cancer risk. Interestingly, Shu and colleagues (34) found that soy food consumption was significantly associated with decreased risk of death and recurrence in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Fink and colleagues (32) reported a decreased allcause mortality in patients with pre-and postmenopausal breast cancer who had a high intake of isoflavones, whereas a reduced breast cancer-related mortality was observed in postmenopausal women. However, the DietCompLyf study (33), which investigated associations between phytoestrogens and breast cancer recurrence and survival, found no significant associations between prediagnosis phytoestrogen intake and reduced breast cancer risk. Interestingly, Shu and colleagues (34) found that soy food consumption was significantly associated with decreased risk of death and recurrence in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Users shall be able to complete the DietCompLyf [5] food frequency questionnaire to create a health profile of their dietary habits. FR6.…”
Section: ) Functional Requirements[user Profile]mentioning
confidence: 99%
“…DietCompLyf [3], an ongoing study where members of the Cancer Research Group at the University of Westminster undertook principle role as research investigation, was set up to see if diet, complementary therapies and lifestyle factors have an effect on breast cancer survival. Data from 3,159 patients from 56 UK-based hospitals have being studied in terms of their diet and lifestyle and their long term outcomes [5]. The DietCompLyf study has shown that approximately half of all patients with breast cancer make a dietary or lifestyle change within 12 ±3 months following diagnosis [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Epidemiological evidence suggests a lower incidence of breast cancer in Asia relative to that in Western countries and this relationship is due to the high consumption of phytoestrogen-rich foods (soybean and their products) in Asia. Although the relationship between phytoestrogen intake and breast cancer risk is not yet conclusive in epidemiology, ample evidence shows that phytoestrogen-rich plants have a positive effect in decreasing breast tumor incidence.…”
Section: Evidence Of Genus Salvia As a Potential Therapeutic Source Fmentioning
confidence: 99%